General Fisheries Commission for the Mediterranean (Food and Agriculture Organization of the United Nations, 2008)
The book repords the result of the tenth section of The Scientific Advisory Committee (SAC). It acknowledged the progress in strengthening the stock assessment process notably through promoting joint assessment practice as well as the definition and identification of criteria for the priority species and shared stocks. It favoured the trend for the use of the data from trawl survey and requested to pay special attention to the hake (Merluccius merluccius) and associated species in 2008. SAC reviewed fishery management proposals emanating from its Sub-Committees and formulated related advice. The Committee took note of progress achieved with regard to defining fisheries restricted areas and the promotion of activities on the ecosystem approach to fisheries (EAF) and marine protected areas (MPAs). The Committee emphasized the need to implement catch and effort data reporting in the frame of Resolution GFCM/31/2007/1 on Task 1 statistical matrix.